Nilai Diagnostik Adenosine Deaminase (ADA) Cairan Pleura pada Penderita Efusi Pleura Tuberkulosi: [The Value of Adenosine Deaminase of Pleural Fluid in Tuberculosis Patient] - Rizki Nur Amalia; Isnu Pradjoko (Jurnal Respirasi, 2016)
Background: Tuberculosis pleural effusion is the most common extrapulmonary TB after lymphadenitis TB. Limited diagnostic methods make TB pleural effusion hard to diagnose. Adenosine deaminase ADA is an enzyme in purin catabolism process which catalyze adenosine into inosine and deoksiadenosine into deoksiinosin. This process is important in lymphoid cell differentiation. ADA is elevated in TB pleural effusion. Method: This study was a cross sectional analytic observational. Statistic analysis was using two independent samples T test. ROC curve was used to determine cut off value of ADA. Kappa test was used to determined the level of agreement of ADA cut off value. Results: Forty eight samples were included in this study, 18 samples with TB pleural effusion and 30 samples with non TB pleural effusion. There was significant difference between pleural fluid ADA in TB and non TB. Positivity of AFB sputum and MTB culture did not show any significant differences. Cut off ADA value for TB pleural effusion diagnosis was 39,19 with sensitivity 88,9% and spesificity 90%. Conclusion: Examination of ADA level in pleural fluid is a usefull tool to diagnose TB pleural effusion.